Cytokine Production by Circulating Endothelial Progenitor Cells before and after G-CSF Mobilization - Alexander Lykov; Olga Poveschenko; Natalia Bondarenko; Alexander Poveschenko; Irina Kim; Eugenie Pokushalov; Alexander Romanov; Vladimir Konenkov (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2016)
Objective: Bone marrow-derived circulating endothelial cells (EPCs) may migrate in ischemia zone, to stimulate resident progenitor cells to proliferation, differentiation and migration in a damage zone, and reduce an ischemia zone through formation of new vessels. Granulocyte colony stimulating factor (G-   CSF) is well established to mobilize hematopoietic stem cells and might, thereby, also increase the pool of endogenously circulating EPCs. EPCs secrete pro-angiogenic factors. Therefore, we investigated the effects of G-CSF administration on mobilization and functional activities of bloodderived EPC in patients with chronic ischemic heart disease (CIHD). Methods and Results: Ten patients with CIHD receive 300 μg per day subcutaneous G-CSF injection for 5 days. The number of EPCs, colony-forming capacity, tube formation and cytokine release were analyzed before and after G-CSF therapy. At day 5 of G-CSF treatment, the number of circulating CD34+CD45- and CD34+CD133+ and CD34+KDR+ cells significantly increased in patients with CIHD. Also, G-CSF therapy augmented the colony-forming capacity and tube formation by EPCs. Likewise, G-CSF treatment augmented cytokine production by circulating EPCs. Early EPCs and late EPCs produced a wide range of cytokines, which dependent the culture condition (gelatin-loaded or fibronectin-loaded surface of culture flask) and the days of cultivation (on day 8 or on day 16). Conclusion: G-CSF treatment effectively mobilizes EPCs, which through paracrine factors production may influence at the resident progenitor cells in ischemic zone of heart to stimulate the repair of myocardium through neoangiogenesis.